Necropolítica, racismo e espaço: geografia da violência e morte contra a população “em situação” de rua na Região Metropolitana da Grande Vitória – ES - Zinek, Wesley Cândido (2023)
The phenomenon of the homeless in the main metropolises of capitalist societies begins to compose and reconfigure the landscapes with their urban-chaotic aesthetics, among rubbish, graffiti and old or abandoned buildings, thus becoming a concern geographic. For society, this population is sometimes uncomfortable, sometimes invisible. For the State and its interests, it sometimes assists and sometimes represses. In this sense, based on extremely violent and deadly events against this population segment, this dissertation is oriented to, geographically, research the dynamics of violence and death that this population is exposed to on a daily basis, as well as their socio-spatialsurvival strategies in public spaces. of the Metropolitan Region of Greater Vitória - RMGV. Empirical analyzes in fieldwork in dialogue with an entire theoretical framework lead to the need for a theoretical-methodological articulation of geography with the idea of Foucauldian biopolitics and its consequences, especially Necropolitics. The research points to a situation of widespread violence and death against the homeless that, in a spatiotemporal way, bears the marks of the colonial slave period with consequences in contemporary racism. Just like the racial issue that is characterized as a founding basis in the process of formation of capitalist societies, this phenomenon is also the product of a logic of social inequality and its expressions in capitalist society. However, this is not a simple research object. These are subjects who, beyond mere numbers or objectification, have names, stories and experiences.